Tall Zirāʿa, Jordanien: Archäometrische Forschungen zur Herkunftsbestimmung der Metallfunde im Rahmen des Gadara Region Projects - Lehmann, Peter; Schulze, Marie (e-Forschungsberichte des DAI, 2023)
In the 2014 campaign of the “Gadara Region Project“ several archaeometrical research projects were carried out. This included the on-site analysis of metal finds as well as their grading according to alloy classes. In addition, over 600 glass finds were analysed.